2023
DOI: 10.1017/s1355770x23000050
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and convictions: evidence from India

Terry-Ann Craigie,
Vis Taraz,
Mariyana Zapryanova

Abstract: High temperatures have been shown to affect human cognition and decision-making in a variety of settings. In this paper, we explore the extent to which higher temperatures affect judicial decision-making in India. We use data on judicial decisions from the Indian eCourt platform, merged with high-resolution gridded daily weather data. We estimate causal effects by leveraging a fixed effects framework. We find that high daily maximum temperatures raise the likelihood of convictions and these results are robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In a similar fashion, hot temperatures have been shown to also affect other important cognitive processes, such as decision-making. Studies from the United States and from India both indicate that judges come to different verdicts under high temperatures, 42 , 43 but we warrant that results for the United States have been shown to not be stable due to coding errors and when comprising a larger dataset. 44 Interestingly, the controlled climatic environment of courts does not prevent temperature from influencing these decisions.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In a similar fashion, hot temperatures have been shown to also affect other important cognitive processes, such as decision-making. Studies from the United States and from India both indicate that judges come to different verdicts under high temperatures, 42 , 43 but we warrant that results for the United States have been shown to not be stable due to coding errors and when comprising a larger dataset. 44 Interestingly, the controlled climatic environment of courts does not prevent temperature from influencing these decisions.…”
Section: Introductionmentioning
confidence: 73%
“…Also, we added a vector X for our control variables wind speed, relative humidity and precipitation. As in similar previous studies, 43 we cluster standard errors at the month-by-city level, as this better captures the level of our treatment and allows us to account for potential correlation of regression errors that could arise within the same city across different months and account for underestimation of the variability in our estimates that could result from weather patterns or local events affecting multiple observations within the same city during the same month. Additionally, we tested robustness to alternative clustering at the politician level.…”
Section: Methodsmentioning
confidence: 99%
“…found that an increase in outdoor temperature caused a decrease in immigration judges' propensity to grant asylum in the U.S. However, Spamann (2022) fails to replicate such result, when correcting for coding errors and enlarging the sample Craigie et al (2023). reports that high daily temperatures raise the likelihood of criminal convictions in India, whileEvans and Siminski (2021)…”
mentioning
confidence: 99%